Distribution of ExPEC Virulence Factors, blaCTX-M, fosA3, and mcr-1 in Escherichia coli Isolated From Commercialized Chicken Carcasses - Cyoia, Paula Signolfi; Koga, Vanessa Lumi; Nishio, Erick Kenji; Houle, Sébastien; Dozois, Charles M.; de Brito, Kelly Cristina Tagliari; de Brito, Benito Guimarães; Nakazato, Gerson; Kobayashi, Renata Katsuko Takayama (Frontiers in Microbiology, 2019)
Pathogenic Escherichia coli found in humans and poultry carcasses harbor similar virulence and resistance genes. The present study aimed to analyze the distribution of extraintestinal pathogenic E. coli (ExPEC) virulence factors (VF), blaCTX-M groups, fosA3, and mcr-1 genes in E. coli isolated from commercialized chicken carcasses in southern Brazil and to evaluate their pathogenic risk. A total of 409 E. coli strains were isolated and characterized for genes encoding virulence factors described in ExPEC. Results of antimicrobial susceptibility testing confirmed that the strains were resistant to 𝛽-lactams, fosfomycin, colistin, and others resistance groups. The highest prevalence of VFs was observed in isolates belonging to the CTX-M groups, especially the CTX-M-2 group, when compared to those in other susceptible strains or strains with different mechanisms of resistance. Furthermore, ESBL strains were found to be 1.40 times more likely to contain three to five ExPEC virulence genes than non-ESBL strains. Our findings revealed the successful conjugation between ESBL-producing E. coli isolated from chicken carcass and the E. coli recipient strain J53, which suggested that genetic determinants encoding CTX-M enzymes may have originated from animals and could be transmitted to humans via food chain. In summary, chicken meat is a potential reservoir of MDR E. coli strains harboring resistance and virulence genes that could pose serious risks to human public health.